The Subdominant Eigenvalue of Möbius Monotone Transition Probability Matrix - Pei-Sen Li; Pan Zhao (Axioms)
We establish a Perron–Frobenius-type theorem for the subdominant eigenvalue of Möbius monotone transition matrices defined on partially ordered state spaces. This result extends the classical work of Keilson and Kester, where they considered stochastically monotone transition matrices in a totally ordered setting. Furthermore, we show that this subdominant eigenvalue is the geometric ergodicity rate.